2011
DOI: 10.1371/journal.pone.0027720
|View full text |Cite
|
Sign up to set email alerts
|

LIV-1 Promotes Prostate Cancer Epithelial-to-Mesenchymal Transition and Metastasis through HB-EGF Shedding and EGFR-Mediated ERK Signaling

Abstract: LIV-1, a zinc transporter, is an effector molecule downstream from soluble growth factors. This protein has been shown to promote epithelial-to-mesenchymal transition (EMT) in human pancreatic, breast, and prostate cancer cells. Despite the implication of LIV-1 in cancer growth and metastasis, there has been no study to determine the role of LIV-1 in prostate cancer progression. Moreover, there was no clear delineation of the molecular mechanism underlying LIV-1 function in cancer cells. In the present communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 332 publications
(75 reference statements)
5
82
1
1
Order By: Relevance
“…Circulating soluble 2-m has been identified by our laboratory as a crucial autocrine and paracrine growth-stimulating factor that allows cancer cells to metastasize, or gain access to bone and colonize the skeleton. This action of 2-m is mainly due to its ability to stimulate the expression of RANKL or LIV-1, which was confirmed by the overexpression or knockdown of these genes in human prostate cancer cell lines, with either increased or decreased prostate cancer bone metastasis, respectively [77,78]. We have reported that 2-m activates PKA signaling, mediated by CREB with increased expression of CREB target genes, including OC and BSP, in prostate cancer [30].…”
Section: Roles Of 2-m In Interaction Between Cancer Cells and Bone MIsupporting
confidence: 56%
“…Circulating soluble 2-m has been identified by our laboratory as a crucial autocrine and paracrine growth-stimulating factor that allows cancer cells to metastasize, or gain access to bone and colonize the skeleton. This action of 2-m is mainly due to its ability to stimulate the expression of RANKL or LIV-1, which was confirmed by the overexpression or knockdown of these genes in human prostate cancer cell lines, with either increased or decreased prostate cancer bone metastasis, respectively [77,78]. We have reported that 2-m activates PKA signaling, mediated by CREB with increased expression of CREB target genes, including OC and BSP, in prostate cancer [30].…”
Section: Roles Of 2-m In Interaction Between Cancer Cells and Bone MIsupporting
confidence: 56%
“…According to these authors, an increase in the expression of transporters of this mineral occurs in cells with malignant tumors, including metallothionein, Zip5, Zip6, Zip7, Zip8, and Zip10, producing an influx of zinc into the neoplastic cells, suggesting that its accumulation inside the breast tumor induces processes dependent on this mineral, for example, the activation of MMPs. 39 Lue et al 40 demonstrated that zinc transporter protein denominated LIV-1 belonging to the Zip transporter family was associated with increased MMP-2 and MMP-9 activity in prostate tumor cells. This protein may play a role in both cell growth, by acting as a zinc transporter, as well as the induction of metastasis, by association with matrix metalloproteinases.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…ZIP6 can be a growth factorelicited signaling molecule through its zinc influx functions from the extracellular space, and thereby enhanced zinc influx mediated by altered ZIP6 expression has been shown to be closely associated with invasive and metastatic ability and cancer progression (374,462). Elevated expression of ZIP6 is involved in epithelial-mesenchymal transition (EMT) of breast cancer cells (159), in pancreatic carcinoma (418), and in prostate cancer cells (256). In particular, the intimate association of ZIP6 with breast cancer is supported by a number of studies.…”
Section: F Zip6 (Liv-1 Subfamily)mentioning
confidence: 99%